Gout and erectile dysfunction: Increased carotid intima-media thickness is independently associated with greater likelihood for erectile dysfunction - Ece Yigit,; Serdar Yasar,; Meryem Can,; Zeki Bayraktar, (Archives of Rheumatology, 2024)
Objectives: The study aimed to compare gout patients and healthy subjects in terms of erectile dysfunction, carotid intima-media thickness (CIMT), and other variables and to investigate the relationship between CIMT and erectile dysfunction. Patients and methods: This cross-sectional study was conducted with 134 male gout patients (median age: 56 years; range, 48 to 62 years) and 104 healthy males (median age: 47 years; range, 40.5 to 54.5 years) between September 2022 and June 2023. Age, comorbidities, height, weight, laboratory results, gout treatment data, insulin resistance evaluated by the homeostatic model assessment for insulin resistance, presence and severity of erectile dysfunction evaluated by the six-item International Index of Erectile Function erectile function domain (IIEF-EF), and CIMT measured by ultrasound were assessed. Results: Hypertension, hyperlipidemia, greater insulin resistance, erectile dysfunction, and bilaterally increased CIMT were significantly more common in the gout group. The mean IIEF-EF score of gout patients was significantly lower than that of controls. Multivariable logistic regression revealed increased CIMT as the sole parameter independently associated with erectile dysfunction (p=0.010). When both groups were categorized into CIMT-based subsets, erectile dysfunction was present in 97.9% of patients with coexistence of gout and increased CIMT (≥0.9 mm), a significantly higher proportion compared to the other three subsets (p<0.001). Conclusion: Increased CIMT was the only factor independently associated with a greater likelihood of erectile dysfunction in patients with and without gout; however, coexistence of gout and increased CIMT appears to result in a significantly elevated risk for erectile dysfunction.